Kualitas Pelayanan Pasien di Unit Gawat Darurat (UGD) : Studi Kualitatif di Puskesmas Sentani Kota Kabupaten Jayapura - Rahmat Nurjaman; Alienra Davry Nanda Kadun MT (Studi Administrasi Publik dan ilmu Komunikasi, 2026)
This study aims to assess the quality of patient care at the Emergency Unit of Sentani City Community Health Center, Jayapura Regency, by examining the experiences and perceptions of patients, their families, and healthcare workers regarding the service. The study used a qualitative approach with a descriptive design. Informants were selected using purposive sampling involving ER patients, their families, and healthcare workers involved in the ER service process at Sentani Community Health Center. Data were collected through in-depth interviews, non-participatory observation, and documentation studies. The data obtained were analyzed qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The research analysis refers to seven dimensions of service quality, namely direct evidence (tangibles), reliability, responsiveness, assurance, empathy, service accessibility, and service systems and flows. The results of the study showed that service quality at the Sentani Community Health Center ER was in the fairly good category, especially the dimensions of empathy, reliability, and responsiveness of healthcare workers. Healthcare workers were friendly, responsive, and provided fair services without discriminating against patient backgrounds. However, a number of obstacles are still found that affect the optimization of services, including limited facilities and infrastructure, the number of health workers that is not commensurate with the service load, patient waiting times in certain conditions, the operating hours of the Emergency Room that are not yet 24 hours, and the low understanding of some patients regarding the applicable service system and flow.